100 Integration of the Group of Student Leaders to the Title V Medical Sciences Campus (MSC) Project from the University of Puerto Rico (UPR) to collaborate in increasing the number of undergraduate (UgS) and graduate students (GS) from Puerto Rico with the knowledge, skills, abilities and opportunities in Clinical and Translational Research (CTR) - Juan C Soto-Santiago; Rico Edgardo L Rosado-Santiago; Rico Rubon; Garcia Garcia; Rico Lizbelle De Jesus-Ojeda (Journal of Clinical and Translational Science, 2023)
OBJECTIVES/GOALS: A group of leading students was integrated as part of the collaborators of the Title V MSC Project with the objective of promoting UgS and GS from Puerto Rico to start and get involved in CTR with an interdisciplinary approach (IA) through the course of INTD 5998: Clinical and Translational Research: Introduction and Principles. METHODS/STUDY POPULATION: The Title V MSC Project of the UPR institutionalized the INTD 5998 course. This course offers UgS and GS the opportunity to start and get involved in CTR. Students with leadership from different universities and from different geographic regions of Puerto Rico were identified and recruited to collaborate in the recruitment of students interested in taking the INTD 5998 course. Since April 2022, the student leaders implemented different strategies to make known about the course and its benefits among their peers. RESULTS/ANTICIPATED RESULTS: For the course of INTD 5998 that began in August 2022, they achieved a contact list of 97 interested students from different geographic areas of Puerto Rico, 21 students applied for the course and 15 enrolled (71% of those who applied and 75% of the maximum course quota). DISCUSSION/SIGNIFICANCE: The student leaders have been an effective promotion and marketing strategy to make known the INTD 5998 course among their peers from the different Universities of Puerto Rico. Their integration as collaborators to the Title V MSC Project has been successful and valuable.